2021
DOI: 10.3390/pathogens10060702
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiont Capture, a Repeated Process of Endosymbiont Transfer with Replacement in Trypanosomatids Angomonas spp.

Abstract: Trypanosomatids of the subfamily Strigomonadinae bear permanent intracellular bacterial symbionts acquired by the common ancestor of these flagellates. However, the cospeciation pattern inherent to such relationships was revealed to be broken upon the description of Angomonas ambiguus, which is sister to A. desouzai, but bears an endosymbiont genetically close to that of A. deanei. Based on phylogenetic inferences, it was proposed that the bacterium from A. deanei had been horizontally transferred to A. ambigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The importance of Strigomonadinae led to the establishment of the first genetically-trackable system in the model species, A. deanei [ 114 ]. A recent study using genomic data of two A. ambiguus strains, A. deanei , and their endosymbionts demonstrated that bacteria from the latter species repeatedly replaced bacteria in the former [ 115 ].…”
Section: Strigomonadinaementioning
confidence: 99%
“…The importance of Strigomonadinae led to the establishment of the first genetically-trackable system in the model species, A. deanei [ 114 ]. A recent study using genomic data of two A. ambiguus strains, A. deanei , and their endosymbionts demonstrated that bacteria from the latter species repeatedly replaced bacteria in the former [ 115 ].…”
Section: Strigomonadinaementioning
confidence: 99%